Bucking the inequality gradient through early child development. (10th February 2010) - Hertzman, Clyde; Siddiqi, Arjumand; Hertzman, Emily; Irwin, Lori G; Vaghri, Ziba; Houweling, Tanja A J; Bell, Ruth; Tinajero, Alfredo; Marmot, Michael
Abstract : A good start in life is the key to reducing health and social inequalities in society. Clyde Hertzman and colleagues argue that governments in rich and poor countries should be investing more in programmes to support early child development